Beta-Naphthoflavone protects from peritonitis by reducing TNF-alpha-induced endothelial cell activation. (December 2015) - Hsu, Sheng-Yao; Liou, Je-Wen; Cheng, Tsung-Lin; Peng, Shih-Yi; Lin, Chi-Chen; Chu, Yuan-Yuan; Luo, Wei-Cheng; Huang, Zheng-Kai; Jiang, Shinn-Jong
Graphical abstract: Abstract: β-Naphthoflavone (β-NF), a ligand of the aryl hydrocarbon receptor, has been shown to possess anti-oxidative properties. We investigated the anti-oxidative and anti-inflammatory potential of β-NF in human microvascular endothelial cells treated with tumor necrosis factor-alpha (TNF-α). Pretreatment with β-NF significantly inhibited TNF-α-induced intracellular reactive oxygen species, translocation of p67 phox, and TNF-α-induced monocyte binding and transmigration. In addition, β-NF significantly inhibited TNF-α-induced ICAM-1and VCAM-1 expression. The mRNA expression levels of the inflammatory cytokines TNF-α and IL-6 were reduced by β-NF, as was the infiltration of white blood cells, in a peritonitis model. The inhibition of adhesion molecules was associated with suppressed nuclear translocation of NF-κB p65 and Akt, and suppressed phosphorylation of ERK1/2 and p38. The translocation of Egr-1, a downstream transcription factor involved in the MEK-ERK signaling pathway, was suppressed by β-NF treatment. Our findings show that β-NF inhibits TNF-α-induced NF-kB and ERK1/2 activation and ROS generation, thereby suppressing the expression of adhesion molecules. This results in reduced adhesion and transmigration of leukocytes in vitro and prevents the infiltration of leukocytes in a peritonitis model. Our findings also suggest that β-NF might prevent TNF-α-induced inflammation.